Simulation of heat flow in a direct-chill caster using comsol multiphysics - Lee, Wei Loon (2016)
Melt-conditioned direct chill (MC-DC) casting process is a novel billet casting technology developed recently for enhanced the grain refinement of cast billet without any grain refiner required. Present work endeavours to understand the behaviour of various parameters of rotor-stator based shearing device on the liquid above the solidification front of AZ31 Mg-alloy billet casting process. It has been found that the influence of increasing rotor speed on the extremely high casting speed has still remained unknown and no one has studied the effect of device diameter and depth of immersion on the billet temperature sump profile. In this work, industrial scale models of both the conventional direct chill (DC) and the (MC-DC) processes were generated by using COMSOL Multiphysics software, in order to study the effect of various parameters on the rotor-stator device for the first time. The results have revealed that the billet temperature distribution in the liquid sump profile is minimized significantly in that case of MC-DC model compared to the conventional DC model. This approach also investigated and revealed the effect of device diameter and depth of immersion of device on the temperature gradient of sump profile. The simulation results can predict the outcome based on various parameters and this is very useful in order to optimize the parameters for maximizing the cast billet quality and improve production line for the industry.